2009
DOI: 10.1007/s11056-009-9178-z
|View full text |Cite
|
Sign up to set email alerts
|

Vermicompost enhances germination of the maritime pine (Pinus pinaster Ait.)

Abstract: We investigated the effect of vermicompost on the germination and early development of six different progenies of the maritime pine (Pinus pinaster Ait.). We compared the effects of incorporating solid vermicompost into the potting media to those of vermicompost water extract to asses the extent of not physically-mediated positive effects. The incorporation of vermicompost in the growing media of maritime pine increased germination by 16%, and particularly, addition of vermicompost water extract produced the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 34 publications
4
35
0
2
Order By: Relevance
“…The effects of various types of VCs with different contents have been investigated on the agricultural crop yield and plant resistance of vegetables such as Indian spinach (Geodakian and Erofeeva, 1996;Ndegwa and Thompson, 2001), garlic (Argüello et al, 2006), strawberries , tomatoes (Atiyeh et al, 1999(Atiyeh et al, , 2000(Atiyeh et al, , 2001Hashemimajd et al, 2004;Gutierrez-Miceli et al, 2007), peppers (Arancon et al, 2005), corn , eggplant (Gajalakshmi and Abbasi, 2004) and fruits such as papaya and banana (CabanasEchevarria et al, 2005;Acevedo and Pire, 2004). In addition, there have been studies on the effects of VC on the seed germination and development of ornamental plants, such as ammaranthus (Dönmez and Allahverdi, 2007), petunias (Arancon et al, 2008), and chrysanthemum (Hidalgo and Harkess, 2002), and of park and forest plants, such as Anatolian black pine (Atik et al, 2009), maritime pine (Lazcano et al, 2010a(Lazcano et al, , 2010b, acacia and eucalyptus (Donald and Visser, 1989), oriental beech (Atik, 2013a). Edwards et al (2004) and Lazcano et al (2009) reported that VC showed positive effects on root and shoot development and leaf area in vegetative propagation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of various types of VCs with different contents have been investigated on the agricultural crop yield and plant resistance of vegetables such as Indian spinach (Geodakian and Erofeeva, 1996;Ndegwa and Thompson, 2001), garlic (Argüello et al, 2006), strawberries , tomatoes (Atiyeh et al, 1999(Atiyeh et al, , 2000(Atiyeh et al, , 2001Hashemimajd et al, 2004;Gutierrez-Miceli et al, 2007), peppers (Arancon et al, 2005), corn , eggplant (Gajalakshmi and Abbasi, 2004) and fruits such as papaya and banana (CabanasEchevarria et al, 2005;Acevedo and Pire, 2004). In addition, there have been studies on the effects of VC on the seed germination and development of ornamental plants, such as ammaranthus (Dönmez and Allahverdi, 2007), petunias (Arancon et al, 2008), and chrysanthemum (Hidalgo and Harkess, 2002), and of park and forest plants, such as Anatolian black pine (Atik et al, 2009), maritime pine (Lazcano et al, 2010a(Lazcano et al, , 2010b, acacia and eucalyptus (Donald and Visser, 1989), oriental beech (Atik, 2013a). Edwards et al (2004) and Lazcano et al (2009) reported that VC showed positive effects on root and shoot development and leaf area in vegetative propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Edwards et al (2004) and Lazcano et al (2009) reported that vermicompost showed positive effects on root and shoot development and leaf area in vegetative propagation. There have been studies on the effects of vermicompost on the seed germination and development of ornamental plants, such as ammaranthus (Dönmez and Allahverdi, 2007), petunias (Arancon et al, 2008), and chrysanthemum (Hidalgo and Harkess, 2002), and of park and forest plants, such as Anatolian black pine (Atik et al, 2009), oriental beech (Atik, 2013a), maritime pine (Lazcano et al, 2010b(Lazcano et al, , 2010c, acacia and eucalyptus (Donald and Visser, 1989). To scientifically define vermicompost fertiliser as an alternative type of organic fertiliser, more studies related to its favourable effects on plant growth, crop yield, and quality are needed, although there are already a considerable number of studies on the effects of compost fertilisers on plant growth and soil (Vivas et al, 2009;Lazcano et al, 2008;Lazcano and Domínguez, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Najar and Khan (2013a) also reported an increase in germination of L. esculentum by 10.33 % with the application of macrophyte-based vermicompost. According to Zaller (2007) and Lazcano et al(2010), increase in seed germination of Rumex obtusifolius by 48 % and Pinus pinaster by 16 % has been reported with the application of cattle manure and rabbit manure vermicompost, respectively. Germination is an internally regulated process influenced mainly by genotype, although external factors such as light period, temperature, moisture and presence of certain chemical compounds can also alter this process either through promotion or inhibition (Kucera et al 2005).…”
Section: Germinationmentioning
confidence: 99%
“…Vermicomposts, whether used as soil additives or as components of greenhouse bedding plant container media, have improved seed germination and enhanced seedling growth and development with overall increase in plant productivity. The beneficial effects include, but are not limited to stimulation of seed germination (Atiyeh et al 2000b;Arancon et al 2007a;Lazcano et al 2010), activation of growth (Lazcano et al 2009;Uma and Malathi 2009), protection against pathogens (Singh et al 2003;Rivera et al 2004;Zaller 2006), nematodes (Serfoji et al 2010) and herbivores (Yardim et al 2006;Arancon et al 2007b;Edwards et al 2010), and increasing overall crop productivity (Nattudurai et al 2013;Gutierrez-Miceli et al 2007;Singh et al 2008;Azarmi et al 2009). Several studies have assessed the effect of vermicompost amendments on the growth of a wide range of marketable fruits cultivated in greenhouses (Arancon et al 2003(Arancon et al , 2004aAtiyeh et al 2000c), as well as in fields (Najar and Khan 2013a;Wang et al 2010;Singh et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Trays were randomly disposed in a greenhouse with daily temperature fluctuating from 18 to 26 1C. Germination and ontogenic development were followed every 2-3 days as in Lazcano et al (2010), and when the first set of true juvenile needles began to elongate, seedlings were harvested and shoot and root dry weight (7 days, 80 1C) were determined. Total dry weight (TDW) and root/shoot ratio (RSR) were derived from these values.…”
Section: Cone and Seed Sampling Processing And Sowingmentioning
confidence: 99%